The heat kernel Lefschetz fixed point formula for the spin-c dirac operator - Duistermaat, Johannes Jisse 1942-; Duistermaat, J. J. 1942- (Johannes Jisse).; SpringerLink (Online service). (New York Birkhäuser, 2011)
Interest in the spin-c Dirac operator originally came about from the study of complex analytic manifolds, where in the non-Kähler case the Dolbeault operator is no longer suitable for getting local formulas for the Riemann-Roch number or the holomorphic Lefschetz number. However, every symplectic manifold (phase space in classical mechanics) also carries an almost complex structure and hence a corresponding spin-c Dirac operator. Using the heat kernels theory of Berline, Getzler, and Vergne,this workrevisits some fundamental concepts of the theory, and presents the application to symplectic geometry.
1 Introduction -- 2 The Dolbeault-Dirac Operator -- 3 Clifford Modules -- 4 The Spin Group and the Spin-c Group -- 5 The Spin-c Dirac Operator -- 6 Its Square -- 7 The Heat Kernel Method -- 8 The Heat Kernel Expansion -- 9 The Heat Kernel on a Principal Bundle -- 10 The Automorphism -- 11 The Hirzebruch-Riemann-Roch Integrand -- 12 The Local Lefschetz Fixed Point Formula -- 13 Characteristic Case -- 14 The Orbifold Version -- 15 Application to Symplectic Geometry -- 16 Appendix: Equivariant Forms.
Electronic reproduction.
Keywords: Almost complex manifolds; Operator theory; Dirac equation; Differential topology; Mathematical physics; Electronic book